2022
DOI: 10.1016/j.neuron.2021.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages transfer mitochondria to sensory neurons to resolve inflammatory pain

Abstract: Highlights d Macrophages accumulate in dorsal root ganglia during resolution of inflammatory pain d These CD206 + M2-like macrophages resolve transient inflammatory pain d Macrophages transfer mitochondria to neurons through vesicles to resolve pain d Pain resolution and mitochondrial transfer need macrophage CD200R and neuronal Isec1 Authors Michiel van der Vlist, Ramin Raoof,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 93 publications
0
81
1
1
Order By: Relevance
“…Recent evidence also suggests that CD200R1 can engage ligands other than CD200, such as iSEC1 and iSEC2 [ 39 , 40 ], generating more challenging conditions to unravel the function of this immune receptor. The expression of iSEC1 and iSEC2 were initially described as being restricted to epithelial cells of the digestive tract [ 39 ] and just very recently iSEC1 mRNA has been shown to be expressed by sensory neurons of the dorsal root ganglia [ 40 ] and in some endothelial cells [ 30 ]. It was reported to be involved in the transport of mitochondria from macrophages to neurons [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence also suggests that CD200R1 can engage ligands other than CD200, such as iSEC1 and iSEC2 [ 39 , 40 ], generating more challenging conditions to unravel the function of this immune receptor. The expression of iSEC1 and iSEC2 were initially described as being restricted to epithelial cells of the digestive tract [ 39 ] and just very recently iSEC1 mRNA has been shown to be expressed by sensory neurons of the dorsal root ganglia [ 40 ] and in some endothelial cells [ 30 ]. It was reported to be involved in the transport of mitochondria from macrophages to neurons [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of iSEC1 and iSEC2 were initially described as being restricted to epithelial cells of the digestive tract [ 39 ] and just very recently iSEC1 mRNA has been shown to be expressed by sensory neurons of the dorsal root ganglia [ 40 ] and in some endothelial cells [ 30 ]. It was reported to be involved in the transport of mitochondria from macrophages to neurons [ 40 ]. This fact could suggest that problems in the transport of mitochondria by blocking CD200R1 could lead to a failed energy boost needed by axons after nerve injury and thus lead to problems in conduction velocity that could result in the impaired locomotor function recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria-rich m/lEVs structures were consistent with published reports (3134). Prior studies have demonstrated that mitochondria or mitochondrial components such as mtDNA, mitochondrial proteins were secreted into the extracellular milieu and transferred between cells (32, 34, 5560). For instance, mesenchymal stem cell-derived-m/lEVs transferred mitochondria into the recipient macrophages leading to increased cellular bioenergetics (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether inhibition of Nox2 might have a therapeutic potential in the treatment of neuropathic pain or other pain conditions needs to be elucidated in further studies. Nonetheless, one also has to consider the fact that Nox2-dependent superoxide production is essential for an appropriate host defense and that it plays a critical role in the resolution of inflammation [ 49 , 60 , 96 , 97 , 98 , 99 ]. Hence, Nox2-inhibiting therapeutic strategies might be associated with various unwanted side effects.…”
Section: Nadph Oxidases Affect Pain Processing By Distinct Mechanismsmentioning
confidence: 99%